ANALISIS STRUKTUR KELENGKAPAN DAN KUALITAS KOMPONEN PENYUSUN LEMBAR KEGIATAN SISWA (LKS) MATERI ANATOMI TUMBUHAN - Rahmawati Rahmawati Rahmawati; Bambang - Supriatno; Sri - Anggraini (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sriwi, 2021)
This research was conducted to determine the structure of the completeness and quality of the worksheets, based on the Vee diagram, to describe the results of the analysis and to describe the reconstruction of the worksheets based on theoretical basis, work steps, data recording, and practical questions consisting of theory, facts, concepts and principles of learning. This study used a qualitative descriptive method with 9 sample worksheets determined by purposive sampling. The first step of this research is to test practicum in accordance with the available worksheets, then to analyze the worksheets using an analytical instrument adapted based on the Vee Diagram (Novak & Gowin, 1984). The results of the study stated that there were several errors found in the worksheets, namely in the tools and materials where the units were not clear and the work steps of the practicum often contained double meanings. Therefore, generally the structure of the worksheet in Plant Anatomy Structure consists of theoretical bases, practical work steps, data recording, and practicum questions consisting of theories, facts, concepts and principles in order to build and reconstruct student knowledge.